Liquid‐Metal Electrodes: Autonomous Surface Reconciliation of a Liquid‐Metal Conductor Micropatterned on a Deformable Hydrogel (Adv. Mater. 37/2020). Issue 37 (15th September 2020) - Park, Jung‐Eun; Kang, Han Sol; Koo, Min; Park, Cheolmin
Abstract : In article number 2002178, Cheolmin Park and co‐workers develop micropatternable, superstretchable, self‐healable, and water‐swellable liquid‐metal electrodes with a low electrical resistance, utilizing the autonomous surface reconciliation of the liquid metal on chemically modified hydrogels. These electrodes are suitable for a variety of deformable microelectronic applications.